Assessment of serum cystatin C in the early detection of type 2 diabetic nephropathy in Cotonou, Benin - Vigan, Jacques; Ahoui, Séraphin; Agboton, Bruno Léopold; Sabi, Kossi Akomola; Tia, Weu Mélanie; Tchaba, FB Rodolphe; Djrolo, François (African Journal of Nephrology, 2019)
Introduction: Diabetic nephropathy is a frequent and dreaded complication of diabetes mellitus. The purpose of this work was to study the role of serum cystatin C in the early detection of diabetic nephropathy among type 2 diabetic patients. Methods: This was a cross-sectional study conducted in Cotonou over a period of six months. Blood samples were tested at the regional food safety testing analysis laboratory. Type 2 diabetic patients older than 15 years, who gave their informed consent, were included in the study. Patients with proven proteinuria, acute kidney injury, haematuria, a positive urine test for nitrite, or reduced glomerular filtration rate <60 mL/min/1.73 m2 were excluded from the study. All patients were subjected to serum cystatin C and microalbuminuria assays. Results: Eighty-eight patients were included in the study. Their average age was 50.7 ± 9.6 years and the male to female ratio was 1.4:1. Twenty-four-hour microalbuminuria was positive in 53 (60%) cases whereas serum cystatin C tested positive in only 2 cases. Sensitivity and specificity tests applied to cystatin C showed very low sensitivity (4%) with a positive predictive value of 100% and high specificity (100%) with a negative predictive value of 41%. Conclusions: When compared with 24-hour microalbuminuria, serum cystatin C assay was not sensitive enough to prove suitable for screening for diabetic nephropathy. Serum cystatin C would therefore not be useful for the early detection of nephropathy among type 2 diabetic patients.